Evaluation of Child-Friendly Boarding School Policies - Sahali, Achmad Ahdan; Hazin, Mufarrihul; Amalia, Kaniati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to evaluate the implementation of the Child-Friendly Islamic Boarding School (PRA) policy through a multisite study at the Bahrul Hidayah Islamic Boarding School in Sidoarjo Regency and the Daruttaqwa 1 Islamic Boarding School in Gresik Regency, East Java. These two boarding schools were selected because they represent a hybrid typology that combines Salafi traditions, modern educational systems, and Middle Eastern educational influences. The evaluation was conducted using James E. Anderson’s framework, which encompasses the dimensions of policy substance, policy implementation, and policy impact. This study employed a qualitative approach with a multisite study design. The data consisted of primary and secondary data. Primary data were obtained through in-depth interviews, participatory observation, and analysis of institutional documents and regulations related to the PRA policy, while secondary data were obtained from scientific articles, books, regulations, and other relevant publications. Data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and the drawing and verification of conclusions. Data validity was ensured through triangulation of sources and techniques, member checks, and peer discussions. The research findings indicate that both Islamic boarding schools have understood the substance of the PRA policy and implemented various key components, such as replacing corporal punishment with a p pproach, constructive guidance, internal complaint mechanisms, and outreach programs. However, the formal establishment of a PRA Task Force has not yet been carried out in accordance with regulatory provisions. The implementation of the policy has also had positive impacts, including a decrease in bullying, increased openness among students, and the development of a more dialogic and humanistic parenting style. This study concludes that the implementation of PRA has shown significant progress, although it still requires strengthening through outreach, training, and continuous monitoring by the Ministry of Religious Affairs.